Heat and mass transfer analysis of nonlinear mixed convective hybrid nanofluid flow with multiple slip boundary conditions - Xia Wei-Feng; Ahmad Shafiq; Khan Muhammad Naveed; Ahmad Hijaz; Rehman Aysha; Baili Jamel; Gia Tuan Nguyen (Elsevier Ltd, 2022)
The current study focuses on the 3D nonlinear mixed convective boundary layer flow of micropolar hybrid nanofluid in the presence microorganism and multiple slip conditions across the slendering surface. The concentration and energy equations are developed in the occurrence of activation energy and joule heating effect. The aim of this research is to consider the Carbon nanotubes (CNTs) which are favored materials in the manufacture of electrochemical devices because of their mechanical and chemical stability, good thermal and electrical conductivities, physiochemical consistency, and featherweight. By keeping such extraordinary properties of carbon nanotubes in mind, we investigate the flow of hybrid nanofluid having MWCNT (multi-wall carbon nanotubes) and SWCNT (single-wall carbon nanotubes). Using an appropriate similarity variable, the flow model (PDEs) are converted into nonlinear ordinary differential equations. The bvp4c approach is utilized to tackle the coupled differential equations. The impact of emerging parameter on temperature distribution, velocity field, concentration distribution, and microorganism field are presented graphically. It is noted the stronger values of wall thickness parameter and Hartmann number produces retardation effect, as a result fluid velocity declines for both SWCNT (single-wall carbon nanotubes) and MWCNT (multi-wall carbon nanotubes) hybrid nanofluid. Furthermore, the transport rate of heat and mass improves by the higher values of for φ2 both simple and hybrid nanofluid.